Keratoconus in young people with learning disabilities: an 'invisible' problem. - Woodhouse, J. Margaret; Watkin, Scott; Kill, Stephen (Learning Disability Practice, 2018)
Keratoconus is a potentially sight-threatening condition in which the cornea distorts and becomes fragile, and without treatment can lead to severe visual impairment. The condition is much more common in people with Down's syndrome and likely to be more common in people with other types of learning disability. Since the advent of a new treatment, corneal cross-linkage, which is only applicable in the early stages of the condition, early diagnosis has become imperative. However, people with learning disabilities are less likely to complain of poor vision and more likely to have poor vision and astigmatism which can mask early changes, so keratoconus can be missed. It is essential that those caring for and supporting people with a learning disability appreciate the risk of keratoconus and ensure that clients have regular and appropriate eye examinations from the age of ten years. When keratoconus is diagnosed it is important to discuss treatment options and for carers to understand the effects of the condition to minimise sight loss and maximise quality of life.